A comparative study of elementary teacher education in the Republic of the Philippines and in the Republic of China - Hsiao, Bernard H. N. (1969)
The study focused on the comparison of elementary teacher education in the Philippine Normal College of the Republic of the Philippines and the Taipei Junior Normal College of the Republic of China. Normative-survey, documentary frequency and interview were used to gather data. Results showed that the training programs provided by P.N.C. is wider than that of T.J.N.C. but T.J.N.C. has a special feature where it has special contributions for the development of elementary school education. The devices taken by P.N.C. were quite limited while the trainees in T.J.N.C. not only enjoyed full scholarship and allowances but also a teaching job after completing their study. The P.N.C. emphasizes on professional education while the T.J.N.C. offers a very flexible percentage of electives.
"October 1969."
Thesis (M.A. Education)--University of the Philippines, Diliman.
Keywords: Teachers -- Training of -- Comparative studies; Teachers -- Training of -- Philippines; Teachers -- Training of -- China